EFFECT OF POSTOPERATIVE PHYSIOTHERAPY INTERVENTION ON QUALITY OF KNEE FUNCTION FOLLOWING FRACTURE OF DISTAL SHAFT OF FEMUR - Patil, Harshada Rajendra; G. Varadharajulu, (International Journal of Psychosocial Rehabilitation, 2020)
This study was undertaken with the aim to determine the Effect of Post-operative physiotherapy intervention on quality of knee function on fracture of distal shaft of femur. The basic objective of this study was to find out the effect of conventional exercises and specific exercises protocol in postoperative fracture of distal shaft of femur patients. This study was done in Krishna hospital, Karad. 26 patients who were diagnosed for postoperative fracture of distal shaft of femur with age group between 18-60years divided into two groups, 23 were males and 3 females. A thorough musculoskeletal assessment was performed and outcome was seen with Range of Motion and SF-36 Scale. First Group A was treated with conventional exercises and Group B was treated with specific exercises protocol for 4 weeks. The pre and post-intervention score was measured with SF-36 Scale.Statistical analysis was done by using Instat software in which Wilcoxon Matched Pairs Test and Mann Whitney Test were used to analyze scores of SF-36 Scale. Statistical analysis revealed that there was extremely significant difference between pre and post values of each group (A and B) (P value=